PENGARUH LIKUIDITAS, PROFITABILITAS, DAN FINANCIAL LEVERAGE TERHADAP TINDAKAN PERATAAN LABA (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2017 – 2019) - Filipus Wicaksono; LMS Kristiyanti; Rukmini Rukmini (ITB AAS INDONESIA, 2021)
The research purpose were determined the effect of liquidity, profitability, financial leverage both simultaneously and individualy on incoming smooting in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This research used a quantitative approach. The data analysis method used multiple linear regression using SPSS test equipment. Hypothetical testing methods used t test, F test, and determination coefficient (R2). Based on the data analysis, can be concluded that 1) liquidity, profitability, and financial leverage simultaneously have a significant effect on the incoming smooting in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period of 2017-2019; 2) liquidity and profitability has not significant effect on incoming smooting in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019; 3) financial leverage significantly affects the incoming smooting in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019; and 4) the ability of independent variables consisting of variable liquidity, profitability, and financial leverage to determine incoming smooting is 71.3%, the remaining 28.7% was explained by other factors not described in the regression model. Keywords: liquidity, profitability, financial leverage, profit leveling